Seed productivity and quality in relation to plant spacing in carrot (Daucus carota) - Pandita, V K; Rana, S C; Chaudhry, Dherendra; Kumar, Vinod (The Indian Journal of Agricultural Sciences, 2005)
The experiment was conducted to find out the effect of plant spacing on seed yield and quality of carrot (Daucus carota L.). In all 9 plant spacing were evaluated during winter season of 2001-02 and 2002-03. Closer spacing of 40 cm x 10 cm or 40 cm x 20 cm improved processed seed yields significantly (32.6%) over wider spacing treatments. The contribution of primary umbels to seed yield was 50 and 28.9% for closer and wider spacing, respectively. The contributionof secondary umbel to seed yield was 63.2% at wider spacing as compared to 48.9% at closer spacing. Seed from closer spacing crop showed lower test weight but seed germination and seedling vigour remained unaffected. The germination of seed from closer spacing crop was considerably higher than the minimum prescribed limit (60%).